Securing cloud data system (SCDS) for key exposure using AES algorithm - Thabet Albatol, Mohammed Samer Hasan (2021)
Nowadays the internet communication playing the imperative role that used to transfer large amount of cloud data in various fields and website applications. In the internet the cloud date and files for the websites transmitted through insecure channel from the sender to the receiver. In the transferring steps of data or files, the third party which called the attackers try to get an illegal access the data without any authorization. Different techniques and methods have been using by private and public sectors in order to protect sensitive cloud data from intruders because the security of electronic data is the crucial issue. Nowadays the recent problem in any website that the attacker tries to break the data confidentiality by acquiring cryptographic keys, means of coercion or backdoors in cryptographic software. The Advanced Encryption Standard (AES) algorithm is one on the most common and widely symmetric block cipher algorithm that used for encryption and decryption data nowadays. The AES algorithm has its own structure to encrypt and decrypt sensitive data that make the attackers difficult to get the real data when encrypting by AES algorithm. In our research project we use to build a local website using the NetBeans Java averments and create our database management by using MySQL language. After that we use to build securing cloud data system (SCDS) for key exposure using the AES algorithm for encrypting and decrypting our website cloud data and files. The website tested by many users that use to register and upload them own data and files using them own e-mails and the unique key that generated after completing the registration. We used to insure for the users data and files in our website by checking the process of our generated system (SCDS) and we got match results for the same files in case of encryption and decryption process.